ANALISIS PENERAPAN ASAS IUS CURIA NOVIT DALAM PUTUSAN PERKARA PERDATA - Lubis, Fauziah; Rangkuti, Nayla Aulia; Moniq, Annisa Sonia; Agatra, Saskya; Isnaini, Wilda; Nazla , Fara (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the application of the ius curia novit principle in civil court decisions in Indonesia. This principle holds that judges are presumed to know the law; therefore, they cannot refuse to adjudicate a case on the grounds that the law does not exist or is unclear. The research employs a normative juridical method using statutory and case approaches. Data were obtained through document analysis of court decisions and legal literature. The results show that the application of the ius curia novit principle is not yet fully effective. Judges often face obstacles such as limited legal knowledge, differences in interpretation, and the influence of living law within society. Several cases also indicate improper application of this principle, particularly in matters that fall outside the court’s jurisdiction. Therefore, there is a need to improve legal understanding, provide judicial training, and strengthen the judicial system to optimize the implementation of this principle.